Weapons Upon Her Body the Female Heroic in the Hebrew Bible. - Collins, Sandra Ladick (Newcastle upon Tyne : Cambridge Scholars Pub., 2012)
The biblical stories of Lot's daughters, Tamar, Ruth and Bathsheba, share much in common - singular women who are left to rely upon their own wits to achieve some measure of victory over the men around them. Scholarly interpretation of these women often reduces them to mere stock characters who inform civic notions about Israel, the perennial underdog who, like these women, achieves against great odds. Or, they reflect the trickery and moral ambiguity inherent in their line as ancestresses of ...
TABLE OF CONTENTS; LIST OF FIGURES; PREFACE; CHAPTER ONE; CHAPTER TWO; CHAPTER THREE; CHAPTER FOUR; CHAPTER FIVE; CHAPTER SIX; APPENDIX A; APPENDIX B; APPENDIX C; APPENDIX D; APPENDIX E; APPENDIX F; APPENDIX G; BIBLIOGRAPHY; INDEX.
Description based on print version record.
Keywords: Christian women -- Religious life; Religion; Women in the Bible -- Biography; Women in the bible; Women in the Bible; RELIGION / Biblical Biography / General; Electronic books